The influence of e-service quality and e-satisfaction on repurchase intention: Mediating role of e-trust - Megayani, Megayani; Chandra, Rama; Haidina, Nur (Jurnal STEI Ekonomi, 2023)
This study aims to determine the role of e-trust in moderating the effect of e-service quality and e-satisfaction on the repurchase intention of Tokopedia's female consumers. This study uses a positive approach and partial least square analysis technique on samples of Tokopedia’s female customers, who have purchased fashion products within the past three months. The sampling method used in this study is purposive sampling, with a total of 100 respondents. First, we find that there is a positive influence of e-service quality on e-trust, e- satisfaction on e-trust and e-trust onrepurchase intention. Second, the mediating role of e-trust has proven statistically significant in predicting the influences of e-service quality and e-satisfaction on repurchase intentions of Tokopedia’s female cunsumers. The limitations of this research is the relatively small sample size and the data are collected from a single online shopping store. Conclusions from this study may not generalize well to the entire online shopping. Our findings imply that the consumer’s e-trust is possibly as antecedent of female cunsumers repurchase intention in online vendors.